An unprecedented 2-D CuSCN coordination network containing both regular and irregular [Cu3(SCN)3] rings supported by a tridentate N-donor ligand - Zhan, Shun-Ze; Peng, Rong; Lin, Shi Hong; Ng, Seik Weng; Li, Dan (Royal Society of Chemistry, 2010)
A neutral 2-D (CuSCN)∞ containing both regular and irregular [Cu3(SCN)3] six-membered rings supported by an asymmetrical tridentate ligand 3,5-bis(3-pyridyl)-1H-pyrazole (Hbppz) were prepared with the formula [Cu3(SCN)3(Hbppz)] ∞. The compound gives strong green luminescence with an emission maximum at 536 nm. © 2010 The Royal Society of Chemistry.